Integrated weed management and herbicide application parameters for herbicide-resistant soybean in Kansas - Lammers, Chad Joseph (Kansas State University, 2022)
Integrated weed management and herbicide application practices were assessed in field and greenhouse studies to improve weed control in herbicide-resistant soybeans (Glycine max (L.) Merr.) grown in Kansas. The field study was conducted to evaluate weed control, soybean yield, and profitability in two herbicide-resistant soybean systems and two row spacings. 2,4-D-, glyphosate-, and glufosinate- resistant (Enlist E3) and isoxaflutole-, glyphosate-, and glufosinate- resistant (LLGT27) soybeans were planted in 38- and 76-cm row spacing for four site-years. Three herbicide treatments were evaluated in each system: pre-emergence herbicide only (PRE), PRE followed by early post-emergence (POST), and POST plus overlapping residual (POR). Weed control was evaluated every 2 weeks after PRE application through R7 soybean. Weed biomass was collected before POST applications and at R7 soybean. Soybean yield was recorded at harvest. Data were subjected to analysis of variance and means separation. In Ottawa during 2020, POST and POR treatments resulted in ≥ 99% control for all species four WAT, while PRE resulted in ≥ 84% control. Similarly, control at Ashland Bottoms was ≥ 90% for POST and POR treatments, while PRE resulted in 7% for isoxaflutole- 62% for 2,4-D-resistant soybeans. All treatments resulted in ≥ 95% control at Scandia in 2021. Row spacing had a minimal effect on weed control and mixed results for yield. In the greenhouse study, the objective was to determine the effect of herbicide combination, optimize carrier volume, and evaluate weed height on weed control. Co-applications of combinations of 2,4-D choline, glyphosate, and glufosinate were applied in carrier volumes of 93-, 140-, and 187- L ha⁻¹ to 5-, 10-, and 20-cm Palmer amaranth (Amaranthus palmeri S. Watson) and large crabgrass (Digitaria sanguinalis L.). Visual ratings and above ground biomass were collected four weeks after treatment. Water-sensitive paper was also sprayed with the same herbicide combinations and carrier volumes to evaluate differences in spray coverage. Data were subjected to analysis of variance and means separation. Carrier volume did not affect Palmer amaranth or large crabgrass control. Control of 5-, 10-, and 20-cm Palmer amaranth was 100%, ≥ 91%, and 6.7 to 79%, respectively, and variation was caused by the herbicide combinations. 2,4-D plus glyphosate provided the greatest Palmer amaranth control. Large crabgrass control pooled for both experiments was ≥ 82% when treatments were applied at 5 cm, but control of 10- or 20-cm large crabgrass was reduced to 51 to 56%. There was a carrier volume by herbicide co-application interaction for the number of droplets deposited and percent area covered on water-sensitive paper. Co-applications containing glufosinate had more droplets than those not containing glufosinate. 2,4-D plus glyphosate had the smallest percent area covered, compared to the other herbicide co-applications. Data from the field study confirms that two-pass herbicide programs are superior to PRE- only programs, regardless of the inclusion of a layered residual herbicide. However, this research did not evaluate the impact of layered residual herbicides on weed seed production, which is crucial for long-term weed management. Results from the greenhouse study suggest that under ideal conditions, carrier volume is less important than herbicide combination and weed size for control of Palmer amaranth and large crabgrass.
Keywords: Integrated weed management; Soybean